Effect of ethanol extract of leaves of Azadirachta indica on palmar arsenical keratosis: A single-blind trial (Bangladesh Journal of Pharmacology, 2014)
The effectiveness of topical application of ethanol extract of Azadirachta indica (neem) daily for 12 weeks was examined in patient of palmar arsenical keratosis. The mean (± SD) score of size of nodules of patients (n=14) using salicylic acid alone before and after treatment were 14.6 ± 4.6 and 10.5 ± 4.5 respectively (28.1% improvement). The mean score of size of nodules of patients (n=15) using salicylic acid plus A. indica (ethanol extract) before treatment was 14.7 ± 4.6 which was decreased to 3.1 ± 2.2 after treatment (79% improvement). The perception score of salicylic acid-treated group was 2.1 whereas it was increased to 4.7 in A. indica plus salicylic acid-treated group. Based on palmar nodular size and patients perception it can be concluded that topical use of ethanol extract of A. indica is effectively in palmar arsenical keratosis.